Development and clinical validity of a novel blood‐based molecular biomarker for subclinical acute rejection following kidney transplant. Issue 1 (31st August 2018) - Friedewald, John J.; Kurian, Sunil M.; Heilman, Raymond L.; Whisenant, Thomas C.; Poggio, Emilio D.; Marsh, Christopher; Baliga, Prabhakar; Odim, Jonah; Brown, Merideth M.; Ikle, David N.; Armstrong, Brian D.; charette, jane I.; et al.
Abstract : Noninvasive biomarkers are needed to monitor stable patients after kidney transplant (KT), because subclinical acute rejection (subAR), currently detectable only with surveillance biopsies, can lead to chronic rejection and graft loss. We conducted a multicenter study to develop a blood‐based molecular biomarker for subAR using peripheral blood paired with surveillance biopsies and strict clinical phenotyping algorithms for discovery and validation. At a predefined threshold, 72% to 75% of KT recipients achieved a negative biomarker test correlating with the absence of subAR (negative predictive value: 78%‐88%), while a positive test was obtained in 25% to 28% correlating with the presence of subAR (positive predictive value: 47%‐61%). The clinical phenotype and biomarker independently and statistically correlated with a composite clinical endpoint (renal function, biopsy‐proved acute rejection, ≥grade 2 interstitial fibrosis, and tubular atrophy), as well as with de novo donor‐specific antibodies. We also found that <50% showed histologic improvement of subAR on follow‐up biopsies despite treatment and that the biomarker could predict this outcome. Our data suggest that a blood‐based biomarker that reduces the need for the indiscriminate use of invasive surveillance biopsies and that correlates with transplant outcomes could be used to monitor KT recipients with stable renal function, including after treatment for subAR, potentially improving KT outcomes. Abstract : The authors present data for a blood‐based gene expression profile that can be used to detect and monitor the treatment of subclinical rejection in patients following kidney transplantation. See Naesens's editorial onpage 5 .